Network+ Guide to Networks - Dean, Tamara (Cengage Course Technology, 2001)
Network+: A Guide to Networks, Second Edition is designed to prepare users for CompTIA's newly-revised 2002 Network+ certification exam, and fully maps to the exam objectives. The book is also an excellent general networking book, covering networking hardware and software, and the soft skills necessary to provide service to internal and external customers. Included in the book are several useful resources that any networking professional would find handy, including a directory of hardware resources, examples of standard networking forms, and a NetWare/Windows NT command reference